Ketahanan Penduduk Usia 7-18 Tahun untuk Menuntaskan Pendidikan di Provinsi Jawa Tengah Tahun 2022 - Firdaus, Alisia; Arcana, I Made (Seminar Nasional Official Statistics, 2023)
The Indonesian government has made efforts for its population to receive at least secondary education through the 12-year compulsory education program. However, not all residents in Indonesia can complete 12 years of education. This indicates the occurrence of school dropouts and affects the resilience of the population to complete education. Central Java Province is one of the provinces whose average length of schooling requires attention because it has the lowest RLS in the Western Region of Indonesia with RLS in 2022 reaching 8.38 years. This study aims to find out the general description of dropping out of school and the resilience to complete education in residents aged 7-18 years in Central Java Province in 2022 and the factors that influence it. The method used is survival analysis with data sourced from the March 2022 Susenas. The results of the research with AFT loglogistics show that gender, head of household education, head of household business field, poverty status, and area of residence have a significant effect on the resilience of the population aged 7-18 years to complete education.